Injury-inciting activities in male and female football players: a systematic review - Aiello, F.; Impellizzeri, F. M.; Brown, S. J.; Serner, A.; McCall, A. (Sports Medicine, 2023)
Background: A comprehensive examination of the sport-specific activities performed around the time of injury is important to hypothesise injury mechanisms, develop prevention strategies, improve management, and inform future investigations. The aim of this systematic review is to summarise the current literature describing the activities performed around the time of injury in football (soccer). Methods: A systematic search was carried out in PubMed, Web of Science, SPORTDiscus, and OpenGrey. Studies were included if participants were football players aged > 13 years old and the activities performed at the time of injury were reported together with the total number of injuries. Risk of bias was assessed using an adapted version of checklists developed for prevalence studies. The activities reported by the studies were grouped to account for inconsistent reporting, and the proportion of each injury activity was calculated. Data were not meta-analysed due to high heterogeneity of methods and classification criteria. Results: We included 64 studies reporting on 56,740 injuries in total. ACL injures were analysed by 12 studies, ankle/foot and knee injuries were analysed by five studies, thigh injuries were analysed by four studies, hip/groin injuries were analysed by three studies, and hamstring injuries were analysed by two studies. Five studies analysed more than one type of injury and 38 studies did not specify the type of injuries analysed. Running and kicking were the predominant activities leading to thigh and hamstring injuries. Changing direction and kicking were the predominant activities leading to hip and groin injuries and duels were the predominant activities leading to ankle injuries. Duels and pressing seem the predominant activities leading to ACL injuries, while results for other knee and general injuries were inconsistent. Conclusions: A qualitative summary of the activities performed at the time of injury has been reported. The results need to be interpreted carefully due to the risk of bias observed in the included studies. If we are to meaningfully progress our knowledge in this area, it is paramount that future research uses consistent methods to record and classify injuries and activities leading up to and performed at the time of injury.